2021
DOI: 10.3390/microbiolres12010001
|View full text |Cite
|
Sign up to set email alerts
|

Acetyleugenol from Acacia nilotica (L.) Exhibits a Strong Antibacterial Activity and Its Phenyl and Indole Analogues Show a Promising Anti-TB Potential Targeting PknE/B Protein Kinases

Abstract: Acetyleugenol is a phytochemical compound with broad effects against infectious diseases and tumors. Here, we extracted, characterized, and elucidated the structure of acetyeugenol, for the first time, from the leaves of Acacia nilotica (L.)—a well-known medicinal plant. The broad antibacterial potential of acetyleugenol was first confirmed against seven bacterial clinical isolates, which reveal a strong activity against Proteus sp., Salmonella typhi, Staphylococcus aureus, and Streptococcus pneumonia with sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…aureus and S. typhi . In a like manner, Cryptomeridiol, a sesquiterpenoid, and Lanosterol along with its derivatives, , have previously been reported to exhibit significant antimicrobial activity against S.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus and S. typhi . In a like manner, Cryptomeridiol, a sesquiterpenoid, and Lanosterol along with its derivatives, , have previously been reported to exhibit significant antimicrobial activity against S.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the authors reported that acetyl eugenol demonstrated to have significant antimicrobial activity against S. aureus and S. typhi . 76 In a like manner, Cryptomeridiol, 77 a sesquiterpenoid, and Lanosterol along with its derivatives, 78 , 79 have previously been reported to exhibit significant antimicrobial activity against S. aureus . In addition to the aforementioned secondary metabolites, there exists a reservoir of antimicrobial secondary metabolites present in the latex, including but not restricted to 1,6-anhydro-β- d -glucopyranose, hexadecanoic acid methyl ester, lupeol, lupeol acetate, and glutinol, which have also been documented to exhibit antimicrobial properties, as outlined in Table 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, acetyl eugenol has been studied for its biological properties, including its antioxidant, anti-inflammatory, and antimicrobial activities [35]. In a study by Abdulhamid et al [36], different fractions were isolated from the leaves of Acacia nilotica L. and tested for antimicrobial activity against seven bacterial clinical isolates: Escherichia coli, Klebsiella pneumoniae, Proteus sp., Pseudomonas aeruginosa, S. aureus, Salmonella typhi, and Streptococcus pneumonia. The results showed that fraction I, whose main component was acetyl eugenol, was effective against all the species tested, especially highlighting its antimicrobial potential against Proteus sp., S. typhi, P. aeruginosa, and S. pneumonia.…”
Section: Main Ceo Components and Their Bioactivitiesmentioning
confidence: 99%
“…40 In contrast, though a wide variety of bioactivities of G14 were reported, no side effect has been discovered yet. 41 Therefore, it is necessary to make G14. Treatment of G13 with acetic chloride afforded G14.…”
Section: Monitoring Chemical Reactionmentioning
confidence: 99%